Desain Pembangkit Listrik Tenaga Surya Off-Grid dan Monitoring Berbasis Node-Red - Arief, Muhammad Baharuddin; Widyartono, Mahendra; Aribowo, Widi; Wardani, Ayusta Lukita (Politeknik Negeri Malang, 2024)
In new renewable energy, the abundant potential of solar energy in Indonesia needs to be utilized effectively, especially in vocational canteens for the purposes of lights and fans. This research aims to design and build an off-grid solar power generation system and Node-Red-based monitoring at the Canteen. The research method used is experimentation through direct observation at the vocational canteen. The tests carried out are the system of SPGS which includes voltage, current, and power and testing monitoring by system sensors and temperature sensors for 5 hours per day in two days. The results obtained are the voltage in the system both panel voltage, AC voltage, and battery voltage are stable and do not exceed the specifications of solar panels. However, the current has increased and decreased although not too drastically and the battery has only decreased by 10%. This is due to the influence of the weather during testing and is not affected by the load power because it does not exceed specifications. In addition, the system sensor has an error of no more than 2% so it can be said that if this system functions optimally and as expected, it can be developed more to save energy.